Finite Plastic Deformations of Orthotropic Circular Plates Under Gaussian Impulse - Anantha Ramu, S.; Janardhana Iyengar, K. (Engineering Transactions, 1978)
The permanent deflection of an orthotropic circular plate subjected to impulse loading is presented. The impulse is assumed to impart a transverse axisymmetric velocity having spatially a general Gaussian distribution. The simultaneous influence of the membrane forces and bending moments is considered in predicting the deformations. It is concluded that the simple bending theory overestimates the final plastic deformation and the time of deformation of the plate. The order of over estimation is not very much dependent upon the spatial distribution of the impulse.